Microphase separation in oriented polymeric chains at the surface of nanomaterials during nanofiber formation. Issue 34 (19th August 2019) - Janghela, Shriram; Devi, Sudeepa; Kambo, Neelu; Roy, Debmalya; Mukhopadhyay, Kingsuk; Prasad, N. Eswara
Abstract : The significance of the configuration of a nanoscale functional surface on the texture of polymeric chain assemblies during electrospinning for controlled flexible scaffolds. Abstract : The presence of low-dimensional functional nanofillers during the formation of morphological phase boundaries in polymeric nanofibers by electrospinning was highlighted in this study. PAN and TPU were both selected with differential viscosities to understand the phase-segregated internal supramolecular structures on functional surfaces of different length scales. The low-dimensional carbon nanofillers displayed a significant role in the topological orientation of the polymeric chains in TPU due to the presence of hard and soft segments in the geometry of TPU. The nano-hybrid shish-kebab-type microphase separation was observed on 1D nanofillers, whereas the anisotropic hierarchical microdomains were formed in the presence of 0D nanofillers. The 2D functional surface produced highly folded nanoscale lamellae by molecular interactions with polymeric chains. By combining different dimensional nanofillers, the hybrid 1D–2D networks created multifaceted structural hierarchies with epitaxial growth on the planar surface and shish-kebab geometry on the 1D functional backbone. Our study has demonstrated the significance of the configuration of nanoscale functional surfaces on the texture of polymeric chain assemblies during electrospinning for controlled flexible scaffolds.